Comparative Evolution of Sand Fly Salivary Protein Families and Implications for Biomarkers of Vector Exposure and Salivary Vaccine Candidates - Coutinho-Abreu, Iliano V.; Valenzuela, Jesus G. (Frontiers in Cellular and Infection Microbiology, 2018)
Sand fly salivary proteins that produce a specific antibody response in humans and animal reservoirs have been shown to be promising biomarkers of sand fly exposure. Furthermore, immunity to sand fly salivary proteins were shown to protect rodents and non-human primates against Leishmania infection. We are missing critical information regarding the divergence amongst sand fly salivary proteins from different sand fly vectors, a knowledge that will support the search of broad or specific salivary biomarkers of vector exposure and those for vaccines components against leishmaniasis. Here, we compare the molecular evolution of the salivary protein families in New World and Old World sand flies from 11 different sand fly vectors. We found that the protein families unique to OW sand flies are more conserved than those unique to NW sand flies regarding both sequence polymorphisms and copy number variation. In addition, the protein families unique to OW sand flies do not display as many conserved cysteine residues as the one unique to the NW group (28.5% in OW versus 62.5% in NW). Moreover, the expression of specific protein families is restricted to the saliva of unique sand fly taxon. The sequences shared between OW and NW sand flies have diverged at similar rates (38.7% and 45.3% amino acid divergence, respectively), yet differences in gene copy number were evident across protein families and sand fly species. Overall, this comparative analysis sheds light on the different modes of sand fly salivary protein family divergence. Also, it informs which protein families are unique and conserved within taxon for the choice of taxon-specific biomarkers of vector exposure, as well as those families more conserved across taxa to be used as pan-specific vaccines for leishmaniasis.